Penentu Niat Membeli Kembali: Perspektif Etika Bisnis Islam - Ma’arif, M. Samsul; Kurniawan, Muhammad; Sisdianto, Ersi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the impact of sensory, emotional, and social experiences on the repurchase intention of consumers using Skintific skincare products in Bandar Lampung, particularly within the context of Islamic ethical business practices.Methodology/Approach: A quantitative research approach was employed, utilizing non-probability sampling techniques. The study involved 104 respondents who had previously used the Skintific products. Data analysis was conducted using descriptive statistics and Partial Least Squares (PLS) to assess the relationships between the variables.Results/Findings: The results indicate that all dimensions of customer experience sensory, emotional, and social have a positive and significant influence on consumers repurchase intentions. This underscores the critical role of customer experience in fostering brand loyalty.Conclusions: Sensory experience, emotional experience, and social experience significantly influence the repurchase intention of skincare consumers in Bandar Lampung, especially when combined with Islamic economic principles that emphasize ethics, fairness, and customer welfare. By implementing these values-based marketing strategies, skincare brands can increase customer loyalty and satisfaction sustainably.Limitations: The study acknowledges certain limitations, including the focus on a specific product and location, which may affect the generalizability of the findings. Additionally, the research highlights the need for further exploration of how Islamic ethical principles can be integrated into marketing strategies to enhance customer experiences.Contributions: This study contributes to understanding how sensory, emotional, and social experiences influence consumers repurchase intention of skincare products in Bandar Lampung. In addition, this study highlights the role of Islamic economic principles in forming ethical and loyalty-oriented marketing strategies.